Xyloketal-derived small molecules show protective effect by decreasing mutant Huntingtin protein aggregates in Caenorhabditis elegans model of Huntington’s disease - Zeng YX; Guo WY; Xu GQ; Wang QM; Feng LY; Long SM; Liang FY; Huang Y; Lu XL; Li SC; Zhou JB; Burgunder JM; et al. (Dove Medical Press, 2016)
Yixuan Zeng,1,2,* Wenyuan Guo,1,* Guangqing Xu,3 Qinmei Wang,4 Luyang Feng,1,2 Simei Long,1 Fengyin Liang,1 Yi Huang,1 Xilin Lu,1 Shichang Li,5 Jiebin Zhou,5 Jean-Marc Burgunder,6 Jiyan Pang,5 Zhong Pei1,2 1Department of Neurology, National Key Clinical Department and Key Discipline of Neurology, Guangdong Key Laboratory for Diagnosis and Treatment of Major Neurological Disease, The First Affiliated Hospital, Sun Yat-sen University, 2Guangzhou Center, Chinese Huntington’s Disease Network, 3Department of Rehabilitation, The First Affiliated Hospital, 4Key laboratory on Assisted Circulation, Ministry of Health, Department of Cardiovascular Medicine of the First Affiliated Hospital, 5School of Chemistry and Chemical Engineering, Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 6Swiss Huntington’s Disease Center, Department of Neurology, University of Bern, Bern, Switzerland *These authors contributed equally to this work Abstract: Huntington’s disease is an autosomal-dominant neurodegenerative disorder, with chorea as the most prominent manifestation. The disease is caused by abnormal expansion of CAG codon repeats in the IT15 gene, which leads to the expression of a glutamine-rich protein named mutant Huntingtin (Htt). Because of its devastating disease burden and lack of valid treatment, development of more effective therapeutics for Huntington’s disease is urgently required. Xyloketal B, a natural product from mangrove fungus, has shown protective effects against toxicity in other neurodegenerative disease models such as Parkinson’s and Alzheimer’s diseases. To identify potential neuroprotective molecules for Huntington’s disease, six derivatives of xyloketal B were screened in a Caenorhabditis elegans Huntington’s disease model; all six compounds showed a protective effect. Molecular docking studies indicated that compound 1 could bind to residues GLN369 and GLN393 of the mutant Htt protein, forming a stable trimeric complex that can prevent the formation of mutant Htt aggregates. Taken together, we conclude that xyloketal derivatives could be novel drug candidates for treating Huntington’s disease. Molecular target analysis is a good method to simulate the interaction between proteins and drug compounds. Further, protective candidate drugs could be designed in future using the guidance of molecular docking results. Keywords: Huntington’s disease, mutant Huntingtin, xyloketal derivatives, Caenorhabditis elegans, protein misfolding, molecular target